Are parental students more likely to develop burnout during undergraduate/graduate studies than non-parental students? - Ásdís Sigurðardóttir 1991- (2019)
The purpose of this research study was to examine if parental university students were more at risk for developing burnout during undergraduate or graduate studies compared to non-parental students at Reykjavík University. Moreover, the difference between gender was examined. Based on previous research students are at risk for developing burnout during studies. Participants were 128 students at Reykjavík University, aged 18-59 years old, studying undergraduate, graduate, doctorate, diploma and university preparation program. Descriptive statistics and independent t-test showed that non-parental students were more likely to develop burnout, as well as, anxiety and depression compared to parental students. Perceived stress had positive correlation on burnout and social support decreased the likelihood of burnout. Moreover, females, regardless of being parental or non-parental students showed to be more receptible to anxiety, depression and burnout than male students. More research is needed to identify risk and protective factors for students. Keywords: Anxiety, depression, burnout, perceived stress, social support, parental students, non-parental students. Markmið rannsóknarinnar var að skoða hvort foreldrar í háskólanámi væru í meiri hættu á að þróa með sér kulnun en samnemendur sem eiga ekki börn. Einnig var skoðaður munurinn á milli kynja, byggt var á fyrri rannsóknum. Þá virðast háskólanemendur í hættu á að þróa með sér kulnun í námi. Þátttakendur voru 128 nemendur við Háskólann í Reykjavík, á aldrinum 18 til 59 ára, í grunnámi, framhaldsnámi, doktorsnámi, diplomanámi og háskólagrunni. Lýsandi tölfræði og óháð t-próf sýndu fram á að líkur á að þróa með sér kulnun í námi væru hærri meðal barnlausra nemenda en foreldra í námi. Skynjuð streita hafði jákvæða fylgni við kulnun og félagsstuðningur hafði hamlandi áhrif á kulnun. Konur, bæði mæður og barnlausar í námi sýndu meiri tilhneigingu til að þróa með sér kvíða, þunglyndi og kulnun samanborið við karlmenn í námi. Þörf er á frekari rannsóknum til að bera ...